2015
DOI: 10.1074/jbc.m115.658468
|View full text |Cite
|
Sign up to set email alerts
|

The Oncoprotein HBXIP Modulates the Feedback Loop of MDM2/p53 to Enhance the Growth of Breast Cancer

Abstract: Background: MDM2 and p53 form a negative feedback loop in regulation. Results: HBXIP up-regulates MDM2 by recruiting p300 to activate transcription factor p53. Conclusion: HBXIP is involved in the MDM2/p53 feedback loop to promote the growth of breast cancer. Significance: Our finding provides a new insight into the mechanism of MDM2/p53 circuit involved in HBXIP in the development of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…In the previous research, we reported that HBXIP could directly stimulate MDM2 transcription in regulation of the MDM2-p53 circuit via acting as a coactivator of p53 transcription factor [28]. Since HBXIP is a multifunctional oncogenic coactivator involved in numerous crosstalks between signaling pathways, we are interested in finding out whether HBXIP can modulate MDM2 or p53 levels by other ways in breast cancer cells.…”
Section: Hbxip Up-regulates Mdm2 Through Decreasing Mir-18b In Breastmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous research, we reported that HBXIP could directly stimulate MDM2 transcription in regulation of the MDM2-p53 circuit via acting as a coactivator of p53 transcription factor [28]. Since HBXIP is a multifunctional oncogenic coactivator involved in numerous crosstalks between signaling pathways, we are interested in finding out whether HBXIP can modulate MDM2 or p53 levels by other ways in breast cancer cells.…”
Section: Hbxip Up-regulates Mdm2 Through Decreasing Mir-18b In Breastmentioning
confidence: 99%
“…It was firstly identified via the interaction with hepatitis B virus X protein, resulting in the suppression of hepatitis B virus replication and modulating the duplication of centrosome in HeLa cells [27]. Our previous study has indicated that HBXIP as an oncopretein recruits the acetyltransferase p300 to p53 in the promoter of MDM2, promoting the MDM2 transcription in breast cancer [28]. It has been reported that HBXIP regulates a large number of transcription factors, such as TF-IID, E2F1, SP1, STAT3, c-Myc, and LXR by serving as an oncogenic transcription coactivator and plays an important role in the development of breast cancer [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Wang F et al’s findings indicate that one of the functions of HBXIP involves proliferation regulation in cancer cell lines and in the normal liver cell line, which is related to cell-cycle transition through checkpoint controls at the G0/G1 or G2/M phases and the downregulation of p27 [18]. Li H et al also found that highly expressed HBXIP accelerates the MDM2-mediated degradation of p53 in breast cancer through modulating the feedback loop of MDM2/p53, resulting in the fast growth of breast cancer cells [19]. Li Y et al have reported that HBXIP promotes the migration of breast cancer cells through increasing filopodia formation involving MEKK2/ERK1/2/Capn4 signaling [20].…”
Section: Discussionmentioning
confidence: 99%
“…BC040587, which locates in chromosome 3q13, harbors various copy number alterations, therefore it suggests BC040587 could be of vital importance in oncogenesis [10,11]. Moreover, dysregulation of BC040587 expression could be a critical step in sarcoma, suggesting an example in tumorigenesis [12] MDM2/P53 negative feedback pathway is notable in cancer research, and it is mainly related to apoptosis as well as proliferation [13]. MDM2 is considered as a notable inhibitor of P53, and its combination with P53 can degrade P53 protein, leading to inactivity of P53 [14].…”
Section: Introductionmentioning
confidence: 99%